Carbon Nanomaterials for Halide Perovskites‐Based Hybrid Photodetectors. Issue 12 (7th October 2020) - Howlader, Ashraful Hossain; Li, Feng; Zheng, Rongkun
Abstract: Over the last few years, metal halide perovskites have established themselves as important materials in the field of optoelectronics. After their first application in photovoltaics, they have been successfully used in other optoelectronic devices, especially photodetectors, owing to their unparalleled optical and electronic properties. Notably, because of their unique optical and electronic properties and small physical dimensions, various carbon nanomaterials have emerged as alternatives for next‐generation optoelectronic devices, and they have also been combined with other materials to realize optimal optoelectronic performance. Some implementations of hybrid photodetectors combining metal halide perovskites with carbon nanomaterials have been reported. Here, it is presented a comprehensive review of the recent advancements in the application of carbon nanomaterials in metal halide perovskite photodetectors, with particular focus on the possible working mechanisms behind the significant enhancement of their performance. First, a brief introduction to the fundamentals of photodetection devices is presented, followed by a short discussion of the intrinsic characteristics of metal halide perovskites and carbon nanomaterials. Detailed descriptions of the operation mechanisms, the evolution of different device structures, and their optoelectronic performance are then given. Finally, the potential challenges and future perspectives for the development of high‐performance stable photodetectors based on these materials are outlined. Abstract : Recent advances in the research field of photodetection technologies based on the composites or hybrids combining metal halide perovskites and carbon nanomaterials are broadly reviewed with emphasis placed on the detailed operating principles and photodetection performances. At the same time, the challenges and scopes for further improvements and development of those hybrid photodetection devices are also presented elaborately.